The Costs of Ambient Cultural Disharmony: Indirect Intercultural Conflicts in Social Environment Undermine Creativity - Chua, Roy Y. J. (Academy of Management Journal, 2013)
Intercultural tensions and conflicts are inevitable in the global workplace. This article introduces the concept of ambient cultural disharmony—indirect experience of intercultural tensions and conflicts in individuals' immediate social environment—and demonstrates how it undermines creative thinking in tasks that draw on knowledge from multiple cultures. Three studies (a network survey and two experiments) showed that ambient cultural disharmony decreased individuals' effectiveness at connecting ideas from disparate cultures. Beliefs that ideas from different cultures are incompatible mediated the relationship between ambient cultural disharmony and creativity. Alternative mechanisms such as negative affect and cognitive disruption were not viable mediators. Although ambient cultural disharmony disrupted creativity, ambient cultural harmony did not promote creativity. These findings have theoretical and practical implications for research in workplace diversity and creativity.